PENGARUH PENGAWASAN, KONDISI KERJA DAN PELATIHAN TERHADAP KINERJA KARYAWAN PADA PT. BUDI PERKASA ALAM MEDAN - Lase, Susi Ratnasari; Sinaga, Ria Veronica; Sembiring, Sabeth (LPPM Universitas Katolik Santo Thomas Medan, 2023)
This research aims to determine and explain the influence of supervision, working conditions and training on employee performance at PT. Budi Perkasa Alam Medan. Data collection was carried out through questionnaires and documentation techniques. The research method used was quantitative, with 51 respondents taken using the Slovin formula. Data analysis in this research used SPSS version 25. From the partial test results, the t test shows that the titing is 2,662 > ttable 1.675 and the significance level is 0.004 < 0.05, proving that supervision has a positive and significant effect on employee performance. thiting 11,438 > ttable 1.675 and a significance level of 0.000 < 0.05 proves that working conditions have a positive and significant effect on employee performance. thiting 3,942 > ttable 1.675 and the significance level is 0.000 < 0.05, proving that training has a positive and significant effect on employee performance. The F test shows Fcount 96,570 > Ftable 2.79 and a significant level of 0.000 < 0.05, proving that supervision, working conditions and training have a positive and significant effect on employee performance. The coefficient of determination (R Square) value is 0.813, meaning that employee performance can be explained by supervision, working conditions and training variables of 81.3, while another 18.7% is explained by other variables not explained in this research such as work ability, communication and work enthusiasm. .